1987
DOI: 10.1136/emj.4.3.155
|View full text |Cite
|
Sign up to set email alerts
|

Virus infection and knee injury.

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This suggests that the prolonged disability reported after Coxsackie B and other virus infections (Behan et al, 1980) was not a cause of poor performance in this group of athletes. There was no relationship between injury and elevated titres to Coxsackie B viruses although a recent study in the West of Scotland (Driscoll et al, 1987) had suggested this as a possibility. In the latter study 58% of a normal control group of individuals had neutralising antibody titres to Coxsackie B 1-5 of 2 256.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This suggests that the prolonged disability reported after Coxsackie B and other virus infections (Behan et al, 1980) was not a cause of poor performance in this group of athletes. There was no relationship between injury and elevated titres to Coxsackie B viruses although a recent study in the West of Scotland (Driscoll et al, 1987) had suggested this as a possibility. In the latter study 58% of a normal control group of individuals had neutralising antibody titres to Coxsackie B 1-5 of 2 256.…”
Section: Discussionmentioning
confidence: 92%
“…A recent investigation was carried out on a group of 12 athletes who presented with loss of form and evidence of viral infection was found in four (Roberts, 1985). In another study, seriological evidence of recent viral infection was sought in patients with knee effusion presenting to an accident and emergency department (Driscoll et al, 1987). Elevated titres of neutralising antibody to Coxsackie B virus were found in patients with spontaneous effusion or with traumatic injury (control group).…”
Section: Introductionmentioning
confidence: 99%